2001
DOI: 10.1248/cpb.49.664
|View full text |Cite
|
Sign up to set email alerts
|

Selective Flotation-Spectrophotometric Determination of Trace Copper(II) in Natural Waters, Human Blood and Drug Samples Using Phenanthraquinone Monophenylthiosemicarbazone.

Abstract: Copper(II) forms 1 : 1 and 1 : 2 intense red complexes with phenanthraquinone monophenylthiosemicarbazone (PPT) at pH 3-3.5 and Ն6.5, respectively. These complexes exhibit maximal absorbance at 545 and 517 nm, the molar absorptivity being 2.3؋10 4 and 4.8؋10 4 l mol ؊1 cm ؊1 , respectively. However, the 1 : 1 complex was quantitatively floated with oleic acid (HOL) surfactant in the pH range 4.5-5.5, providing a highly selective and sensitive procedure for the spectrophotometric determination of Cu II . The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…17 A flotation technique is recommended as an effective and less-expensive separation and preconcentration tool with most of the advancing factors. [18][19][20][21][22] It involves the removal of surface inactive ions from an aqueous solution with the aid of air bubbles using three modes: adsorptive flotation, precipitation flotation or adsorbing-particle flotation. 22 A process based on solid-phase extraction (SPE) has received more acceptance due to a number of possible advantages, including the availability and easy recovery of the solid phase, the attainability of a large preconcentration factor and a facility for separation.…”
Section: Introductionmentioning
confidence: 99%
“…17 A flotation technique is recommended as an effective and less-expensive separation and preconcentration tool with most of the advancing factors. [18][19][20][21][22] It involves the removal of surface inactive ions from an aqueous solution with the aid of air bubbles using three modes: adsorptive flotation, precipitation flotation or adsorbing-particle flotation. 22 A process based on solid-phase extraction (SPE) has received more acceptance due to a number of possible advantages, including the availability and easy recovery of the solid phase, the attainability of a large preconcentration factor and a facility for separation.…”
Section: Introductionmentioning
confidence: 99%
“…contain heavy metals, which are of great environmental concern and must be removed prior to water discharge or water recycling. Copper has received considerable attention owing to its uses in metallurgy, chemical industries and is necessary for other many biological important functions (Freematle, 1989;Khalifa et al, 2001). When levels of Cu exceed certain values, however, defense mechanisms to protect against excess Cu are overcome and toxicity results.…”
mentioning
confidence: 99%
“…The reported list of toxic Cu species (Sorenson, 1991) often includes Cu(OH) + , Cu 2 (OH) 2 2+ and CuCO 3 . However, without doubt, Cu 2+ ions that are present in various aqueous solutions (their presence is a function of pH) are considered to be the most toxic of dissolved copper species (Freematle, 1989;Khalifa et al, 2001;Sorenson, 1991). Excess copper in water is not only harmful to human beings, but also interferes with the self-purification of bulk water (Ghazy et al, 2006) and adverse effect on the microbiological treatment of wastewater .…”
mentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18] Consequently, such a process enabled and facilitated the spectrophotometric determination of the analyte.…”
Section: Flotation-separation Of V(iv)mentioning
confidence: 99%
“…On the other hand, methods for the separation and preconcentration of metals by flotation, followed by their spectrophotometric determination, have increased in popularity in recent years. [9][10][11][12][13][14][15][16][17][18] A literature survey showed that ion-flotation followed by spectrophotometric determination of V(IV) is rarely reported. 19 Also, no attempt has been found for using 1-(2-hydroxy-4-methoxybenzophenone)-4-phenylthiosemicarbazone (HMBPT) in this concern.…”
mentioning
confidence: 99%